AB0007 Association at systemic levels of cytokine mrnas and protein quantities in rheumatoid arthritis. (12th June 2018) - Manolova, I.; Ivanova, M.G.; Vasilev, G.; Stoilov, R.; Miteva, L.; Stanilova, S.
Abstract : Background: Rheumatoid arthritis (RA) is an autoimmune inflammatory disease, characterised by chronic synovitis, bone and cartilage destruction, as well as systemic manifestation. In accordance with the pivotal role of cytokines in autoimmunity and their impact as biomarkers, we analysed gene expression at both mRNA and protein levels of several cytokines in peripheral blood of RA patients. Objectives: The aim of the present study was to investigate the gene expressions at mRNA and protein levels of main pro-inflammatory (TNF-α, IL18, IL-12p40; IL-23, IL-6) and immunosuppressive (TGF-β1 and IL10) cytokines and transcription factor Foxp3 in peripheral blood of RA patients. Methods: Total RNA from peripheral blood was isolated from 32 patients matching the ACR/ EULAR 2010 criteria for RA and 27 healthy controls. Quantitative real-time polymerase chain reaction was performed for the 8 genes of interests, using the TaqMan detection system. Relative quantitative evaluation of mRNAs was performed by the comparative ΔΔCt method and results were presented as n-fold mean difference (RQ-relative quantity) of target genes relative to calibrator (healthy controls) after normalisation to the reference genes (GAPDH and 18srRNA). Serum quantities of cytokines were measured by ELISA. Results: From studied pro-inflammatory cytokine genes, we found down-regulation in the following order: IL6 >TNFA>IL12B; up regulation of IL23A and no change in IL18 gene expression in RA patients group compared to healthy controls. For anti-inflammatory genes we detected significantly increased quantity for IL10 mRNA and no change for TGFB1 mRNA. The most profound down-regulation (more than 7-fold) was observed for IL6 gene (p<0.001), while the serum level of the same cytokine was significantly increased as compared to the same controls. The similar tendency was observed in the expression of TNFA, which gene expression was approximately 2-fold down-regulated, whereas serum levels were increased. IL12B mRNA were slightly but not significantly decreased (RQ=0.709; p=0.169) in RA patients. An upregulation of IL-23 was detected for IL23A gene (RQ=2.422, p=0.002) and serum level of IL-23 as well. TGFB1 mRNA levels were approximately equal in patients and controls in contrast to IL-10, which was upregulated in both mRNA (RQ=1.6; p=0.034) and serum levels (over 6.6 fold; p<0.05). In addition, mRNA expression of FoxP3, a master transcription factor for Treg subset was also down-regulated over 4-fold in RA patients (p<0.001). A positive correlation was found between gene expression of IL6 with Foxp3, TNFA and TGFB1 in RA (r=0.744, p=0.004; r=0.6, p=0.03; r=0.556, p=0.048, respectively). Conclusions: Our results demonstrated significant differences in the expression of mRNA encoded cytokines and their protein quantities at systemic level of RA patients, mostly on IL-23, IL-6 and TNF-alpha. Disclosure of Interest: None declared